2020
DOI: 10.3389/fphar.2020.567518
|View full text |Cite
|
Sign up to set email alerts
|

Mushrooms-Rich Preparations on Wound Healing: From Nutritional to Medicinal Attributes

Abstract: Mushrooms have a significant role in human diet as functional food and as a nutraceutical resource. The combination of its umami flavor, protein, vitamins, minerals and carbohydrates has meant that mushrooms could be considered a cheap food source for a long time in many countries. Moreover, mushrooms contain an excellent variety of bioactive metabolites that can be successful in both prevention and treatment of various human health hazards. In addition, extracts from medicinal mushrooms and their metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Nature may bring us components with wound healing properties (J. Sharifi-Rad, Butnariu, et al, 2020) but technology and investigation are needed to improve these properties. Therefore, in the present review, we focused our attention on the antimicrobial and wound healing properties of nanoformulated curcumin, and we gave a perspective on its therapeutic applications for both microbial infections treatment and in the wound healing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature may bring us components with wound healing properties (J. Sharifi-Rad, Butnariu, et al, 2020) but technology and investigation are needed to improve these properties. Therefore, in the present review, we focused our attention on the antimicrobial and wound healing properties of nanoformulated curcumin, and we gave a perspective on its therapeutic applications for both microbial infections treatment and in the wound healing process.…”
Section: Introductionmentioning
confidence: 99%
“…However, curcumin low aqueous solubility, poor tissue absorption and low bioavailability is a problem which need to be solved through the design of new drug formulations such as curcumin nanoformulations (Kesharwani, Jain, Srivastava, & Keshari, 2020; C. Mohanty & Sahoo, 2017; J. Sharifi‐Rad, El Rayess, et al, 2020). Nature may bring us components with wound healing properties (J. Sharifi‐Rad, Butnariu, et al, 2020) but technology and investigation are needed to improve these properties. Therefore, in the present review, we focused our attention on the antimicrobial and wound healing properties of nanoformulated curcumin, and we gave a perspective on its therapeutic applications for both microbial infections treatment and in the wound healing process.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrition works in accelerate body metabolism to dispose many toxins from the body. 30 Decreasing in liver weight and liver index explained that GACP play role in liver mass via decreasing collagen component which increase the weight of liver. 31 In this study, the degree of liver injury was indicated by measuring the levels of liver enzyme biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The high capacity of the EPSs to capture and release its cargo, such as drugs and proteins, is one of the essential EPSs applications in EPSs-based hydrogels. Nielsen, 2013;Sharifi-Rad et al, 2020). βGs improve wound repair by promoting macrophages infiltration, which motivates tissue granulation, types I and III collagen, and re-epithelialization.…”
Section: Tissue Engineering (Te)mentioning
confidence: 99%